Step
*
1
of Lemma
rv-circle-circle-lemma2
1. n : {2...}
2. r1 : {r:ℝ| r0 ≤ r} 
3. r2 : {r:ℝ| r0 ≤ r} 
4. b : ℝ^n
5. r0 < ||b||
6. ∀b':ℝ^n
     ((b⋅b' = r0)
     
⇒ (||b'|| = ||b||)
     
⇒ ((r1^2 - r2^2) + ||b||^2^2 ≤ (r(4) * ||b||^2 * r1^2))
     
⇒ let c = ((r1^2 - r2^2) + ||b||^2/r(2)) in
         let d = (||b||^2 * r1^2) - c^2 in
         ∀x:ℝ^n
           ((req-vec(n;x;(r1/||b||^2)*c*b + rsqrt(d)*b') ∨ req-vec(n;x;(r1/||b||^2)*c*b - rsqrt(d)*b'))
           
⇒ ((||x|| = r1) ∧ (||x - b|| = r2))))
⊢ ((r1^2 - r2^2) + ||b||^2^2 ≤ (r(4) * ||b||^2 * r1^2))
⇒ (∃u,v:ℝ^n
     (((||u|| = r1) ∧ (||u - b|| = r2))
     ∧ ((||v|| = r1) ∧ (||v - b|| = r2))
     ∧ (((r1^2 - r2^2) + ||b||^2^2 < (r(4) * ||b||^2 * r1^2)) 
⇒ u ≠ v)))
BY
{ Assert ⌜∃b':ℝ^n. ((b⋅b' = r0) ∧ (||b'|| = ||b||))⌝⋅ }
1
.....assertion..... 
1. n : {2...}
2. r1 : {r:ℝ| r0 ≤ r} 
3. r2 : {r:ℝ| r0 ≤ r} 
4. b : ℝ^n
5. r0 < ||b||
6. ∀b':ℝ^n
     ((b⋅b' = r0)
     
⇒ (||b'|| = ||b||)
     
⇒ ((r1^2 - r2^2) + ||b||^2^2 ≤ (r(4) * ||b||^2 * r1^2))
     
⇒ let c = ((r1^2 - r2^2) + ||b||^2/r(2)) in
         let d = (||b||^2 * r1^2) - c^2 in
         ∀x:ℝ^n
           ((req-vec(n;x;(r1/||b||^2)*c*b + rsqrt(d)*b') ∨ req-vec(n;x;(r1/||b||^2)*c*b - rsqrt(d)*b'))
           
⇒ ((||x|| = r1) ∧ (||x - b|| = r2))))
⊢ ∃b':ℝ^n. ((b⋅b' = r0) ∧ (||b'|| = ||b||))
2
1. n : {2...}
2. r1 : {r:ℝ| r0 ≤ r} 
3. r2 : {r:ℝ| r0 ≤ r} 
4. b : ℝ^n
5. r0 < ||b||
6. ∀b':ℝ^n
     ((b⋅b' = r0)
     
⇒ (||b'|| = ||b||)
     
⇒ ((r1^2 - r2^2) + ||b||^2^2 ≤ (r(4) * ||b||^2 * r1^2))
     
⇒ let c = ((r1^2 - r2^2) + ||b||^2/r(2)) in
         let d = (||b||^2 * r1^2) - c^2 in
         ∀x:ℝ^n
           ((req-vec(n;x;(r1/||b||^2)*c*b + rsqrt(d)*b') ∨ req-vec(n;x;(r1/||b||^2)*c*b - rsqrt(d)*b'))
           
⇒ ((||x|| = r1) ∧ (||x - b|| = r2))))
7. ∃b':ℝ^n. ((b⋅b' = r0) ∧ (||b'|| = ||b||))
⊢ ((r1^2 - r2^2) + ||b||^2^2 ≤ (r(4) * ||b||^2 * r1^2))
⇒ (∃u,v:ℝ^n
     (((||u|| = r1) ∧ (||u - b|| = r2))
     ∧ ((||v|| = r1) ∧ (||v - b|| = r2))
     ∧ (((r1^2 - r2^2) + ||b||^2^2 < (r(4) * ||b||^2 * r1^2)) 
⇒ u ≠ v)))
Latex:
Latex:
1.  n  :  \{2...\}
2.  r1  :  \{r:\mBbbR{}|  r0  \mleq{}  r\} 
3.  r2  :  \{r:\mBbbR{}|  r0  \mleq{}  r\} 
4.  b  :  \mBbbR{}\^{}n
5.  r0  <  ||b||
6.  \mforall{}b':\mBbbR{}\^{}n
          ((b\mcdot{}b'  =  r0)
          {}\mRightarrow{}  (||b'||  =  ||b||)
          {}\mRightarrow{}  ((r1\^{}2  -  r2\^{}2)  +  ||b||\^{}2\^{}2  \mleq{}  (r(4)  *  ||b||\^{}2  *  r1\^{}2))
          {}\mRightarrow{}  let  c  =  ((r1\^{}2  -  r2\^{}2)  +  ||b||\^{}2/r(2))  in
                  let  d  =  (||b||\^{}2  *  r1\^{}2)  -  c\^{}2  in
                  \mforall{}x:\mBbbR{}\^{}n
                      ((req-vec(n;x;(r1/||b||\^{}2)*c*b  +  rsqrt(d)*b')
                      \mvee{}  req-vec(n;x;(r1/||b||\^{}2)*c*b  -  rsqrt(d)*b'))
                      {}\mRightarrow{}  ((||x||  =  r1)  \mwedge{}  (||x  -  b||  =  r2))))
\mvdash{}  ((r1\^{}2  -  r2\^{}2)  +  ||b||\^{}2\^{}2  \mleq{}  (r(4)  *  ||b||\^{}2  *  r1\^{}2))
{}\mRightarrow{}  (\mexists{}u,v:\mBbbR{}\^{}n
          (((||u||  =  r1)  \mwedge{}  (||u  -  b||  =  r2))
          \mwedge{}  ((||v||  =  r1)  \mwedge{}  (||v  -  b||  =  r2))
          \mwedge{}  (((r1\^{}2  -  r2\^{}2)  +  ||b||\^{}2\^{}2  <  (r(4)  *  ||b||\^{}2  *  r1\^{}2))  {}\mRightarrow{}  u  \mneq{}  v)))
By
Latex:
Assert  \mkleeneopen{}\mexists{}b':\mBbbR{}\^{}n.  ((b\mcdot{}b'  =  r0)  \mwedge{}  (||b'||  =  ||b||))\mkleeneclose{}\mcdot{}
Home
Index